Discourses of global climate change : apocalyptic framing and political antagonisms - Anshelm, Jonas, 1960-; Hultman, Martin (New York, NY : Routledge, 2015)
'This book examines the arguments made by political actors in the creation of antagonistic discourses on climate change. Using in-depth empirical research from Sweden, a country considered by the international political community to be a frontrunner in tackling climate change, it draws out lessons that contribute to the worldwide environmental debate.The book identifies and analyses four globally circulated discourses that call for very different action to be taken to achieve sustainability: Industrial fatalism, Green Keynesianism, Eco-socialism and Climate scepticism. Drawing on risk society and post-political theory, it elaborates concepts such as industrial modern masculinity and ecomodern utopia, exploring how it is possible to reconcile apocalyptic framing to the dominant discourse of political conservatism. This highly original and detailed study focuses on opinion leaders and the way discourses are framed in the climate change debate, making it valuable reading for students and scholars of environmental communication and media, global environmental policy, energy research and sustainability'--
'This book demonstrates the media's role in the creation of dominant discourses on climate change and examines the arguments made by political actors in the mass media arena. Using in-depth empirical research of Sweden, a country considered by the international political community to be a frontrunner in tackling climate change, the book analyses the worldwide climate change debate. This highly original and detailed study focuses on opinion leaders and the way discourses are framed in the climate change debate, making it valuable reading for students and scholars of environmental communication and media as well environmental policy and politics'--
Includes bibliographical references and index.
Keywords: Climatic changes -- Political aspects -- Sweden; Global warming -- Political aspects -- Sweden; Global environmental change -- Political aspects -- Sweden; Climatic changes -- Press coverage -- Sweden; Global warming -- Press coverage -- Sweden; Global environmental change -- Press coverage -- Sweden